2020
DOI: 10.3390/cancers12051097
|View full text |Cite
|
Sign up to set email alerts
|

Deactivation of Glutaminolysis Sensitizes PIK3CA-Mutated Colorectal Cancer Cells to Aspirin-Induced Growth Inhibition

Abstract: Aspirin is one of the most promising over-the-counter drugs to repurpose for cancer treatment. In particular, aspirin has been reported to be effective against PIK3CA-mutated colorectal cancer (CRC); however, little information is available on how the PIK3CA gene status affects its efficacy. We found that the growth inhibitory effects of aspirin were impaired upon glutamine deprivation in PIK3CA-mutated CRC cells. Notably, glutamine dependency of aspirin-mediated growth inhibition was observed in PIK3CA-mutate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 47 publications
2
6
0
Order By: Relevance
“…We found that GLS expression was negatively associated with the sensitivity of temsirolimus, an mTOR inhibitor. Interestingly, combining the GLS inhibitor with an mTOR inhibitor is reported to result in a combinatorial effect [ 46 , 47 , 48 ]. The upregulation of GLS was reported to be induced following mTOR inhibition, providing a theoretical basis for the combination of GLS inhibitors and mTOR inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…We found that GLS expression was negatively associated with the sensitivity of temsirolimus, an mTOR inhibitor. Interestingly, combining the GLS inhibitor with an mTOR inhibitor is reported to result in a combinatorial effect [ 46 , 47 , 48 ]. The upregulation of GLS was reported to be induced following mTOR inhibition, providing a theoretical basis for the combination of GLS inhibitors and mTOR inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that hepatocellular cell adhesion molecule (HepaCAM) can serve a significant role in tumour cell proliferation, apoptosis, migration and invasion, since its expression is typically absent in cancer tissues ( 19 , 45 ). In addition, previous reports have found that mutation in phosphatidylinositol-4,5-bisphosphate 3-kinase catalytic subunit α ( PIK3CA ) can activate PI3K/AKT signalling downstream to induce alterations in Gln metabolism in tumour cells ( 29 ). In the present study, bioinformatics analyses of various databases were performed to predict the correlation in the expression levels between HepaCAM and PIK3CA.…”
Section: Discussionmentioning
confidence: 99%
“…PIK3CA can be constitutively activated by two main different mechanisms, namely activating mutation and amplification (26). Accumulating evidence has revealed that PIK3CA is associated with Gln metabolism reprogramming in numerous types of cancers (27)(28)(29)(30). Consequently, PIK3CA may also be a key regulatory target for reprogramming Gln metabolism in PCa.…”
Section: Introductionmentioning
confidence: 99%
“…Cell cycle and apoptosis induction were analyzed as previously described [ 40 ]. Briefly, after cells were seeded in 6-well plates at a density of 50,000 cells per well and incubated for 24 h, the cells were treated with the agent or siRNAs and harvested by trypsinization.…”
Section: Methodsmentioning
confidence: 99%